Optimizing Animal Feed Raw Material Inventory Control Using the Min-Max Stock Method as an Effort to Minimize Inventory Costs : Optimalisasi Pengendalian Persediaan Bahan Baku Pakan Ternak Menggunakan Metode Min-Max Stock Sebagai Upaya Meminimalkan Biaya Persediaan - Mahendra Putra Prasetiawan; Dira Ernawati (Academia Open, 2026)
General Background: Reliable raw material control is essential for operational continuity because excessive and insufficient supplies can disrupt production and increase expenditure. Specific Background: Fluctuating demand at an animal feed manufacturer created recurring overstock and stockout conditions for Pollard, Soya Bean Meal, Full Fat Soya, and Crude Palm Oil. Knowledge Gap: The company’s existing policy did not establish coordinated safety quantities, minimum and maximum levels, reorder points, and ordering frequencies based on historical usage. Aims: This study evaluates the Min Max Stock method for controlling four principal broiler feed materials and lowering total expenditure. Historical purchasing and consumption records from May 2025 to April 2026 were collected through observation and documentation. Current company calculations were compared with Min Max Stock calculations, while Weighted Moving Average and Single Exponential Smoothing supported demand forecasting. Results: The proposed approach generated savings of Rp23,850,000 for Pollard, Rp33,125,000 for Soya Bean Meal, Rp15,900,000 for Full Fat Soya, and Rp43,800,000 for Crude Palm Oil, equivalent to reductions of 48%, 45%, 36%, and 49%, respectively. Total savings reached Rp116,675,000, with annual ordering frequencies set at 18, 26, 20, and 23 times. Novelty: The study combines material-level control thresholds, order quantities, forecasting, and expenditure comparison within one operational framework for broiler feed production. Implications: The company should adopt the proposed policy and train relevant staff to maintain material availability while reducing overstock, stockout, and unnecessary expenditure. Highlights: Pollard generated an annual expenditure reduction of Rp23.85 million. SBM and FFS lowered annual spending by Rp33.125 million and Rp15.9 million. CPO achieved the greatest proportional decrease, with 23 planned orders annually. Keywords : Cost, Inventory, Raw Materials, Min-Max Stock